A polyzwitterion-based antifouling and flexible bilayer hydrogel coating. (September 2022) - Wang, Xing-wang; Wang, Jing; Yu, Yan; Yu, Lu; Wang, You-xiang; Ren, Ke-feng; Ji, Jian
Abstract: A coating of implanted medical devices with antifouling ability, preferable mechanical property and stability in the physiological environment proves beneficial for their clinical use. Here we develop a flexible bilayer hydrogel coating with self-healing, antifouling, and lubricating functions. Our bilayer coating consists of two functional layers: i) an adhesive flexible polyelectrolyte hydrogel layer, ii) an antifouling and lubricous polyzwitterionic layer. The bilayer hydrogel coating is prepared in two steps dip-coating and in situ UV photopolymerization. Our results demonstrate that the prepared bilayer hydrogel coating has proper mechanical properties, favorable hydrophilicity, and lower surface friction. We demonstrate that the bilayer hydrogel coating maintains hydrophilicity under extreme condition (1 h sonicating or 5000 times repeating bending). The as-prepared bilayer hydrogel coating resists non-specific protein adsorption, inhibits cell and platelet adhesion, and prevents thrombosis. This work provides a reliable coating on the medical materials, showing a promising practical application in diversified implantable medical devices. Graphical abstract: Image 1